The relationship of age, early motor skills and observable child behaviors in young children with developmental delays. (October 2019) - MacDonald, Megan; McIntyre, Laura Lee
Abstract: Background: Children with disabilities often experience delays in one or more domains of development including motor skill delays. Delays in motor skill development may put children further behind their peers without disabilities in respect to aspects of early learning. Aims: The purpose of this study was to examine how gross motor skills mediated the relationship of age and the observable child behaviors of compliance and adaptive behavior in a group of young children (2–4 years) with developmental disabilities around one time point. Methods: Children with developmental disabilities (N = 113) were assessed on direct measures of motor skills and the child behaviors of compliance and adaptive behavior. Two independent simple mediation analyses were conducted using PROCESS, an ordinary least squares path analysis appropriate for small sample sizes. Results. Age had a positive relationship with gross motor skills (a = .66, p < .001) when the outcome variable was adaptive behavior and age had a positive relationship with gross motor skills (a = .66, p < .001) when the outcome variable was compliance. Conclusions: Motor skill development may promote or hinder development in other childhood behaviors such as compliance and adaptive behavior.